1984
DOI: 10.1055/s-2007-1023382
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Aorto-pulmonary Fistula - Case Report

Abstract: Two reports of the rare condition, acquired aorto-pulmonary fistula, are presented, one the result of acute aortic dissection, the other, giant cell aortitis. The presentation, diagnosis, and management are discussed and the literature reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…To our knowledge, this is only the fifth reported case of Ao-PA fistula due to aortic dissection. Keenan et al [2] have reported a similar case in which a 64-year-old man presented initially with chest pain, syncope and mild hemoptysis. Diagnosis was made by catheterization.…”
Section: Discussionmentioning
confidence: 94%
“…To our knowledge, this is only the fifth reported case of Ao-PA fistula due to aortic dissection. Keenan et al [2] have reported a similar case in which a 64-year-old man presented initially with chest pain, syncope and mild hemoptysis. Diagnosis was made by catheterization.…”
Section: Discussionmentioning
confidence: 94%
“…6) SAPVFs are congenital more than 50% of the time, but some SAPVFs may develop as a consequence of tumors, inflammatory processes of the pleura or lung, or after blunt, open, or iatrogenic chest injuries. [1][2][3][4] SAPVF of the present case developed due to long-standing inflammatory and adhesive processes at the bar removal site. The etiology of SAPVF is generally thought to be due to adhesions that bridge the pleura from the chest wall to the lung, which then may develop new blood vessels that are large enough to cause significant systemic-pulmonary fistulas.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Although most published cases reported internal mammary arteries and intercostal arteries as feeding arteries, only one case reported a SAPVF between the axillary artery and pulmonary vessels. [3][4][5][6][7] We recently encountered a patient with acquired axillary artery to pulmonary artery fistula detected by dualsource 64-slice CT (DSCT) angiography who had a Nuss surgical procedure for pectus excavatum.…”
Section: Introductionmentioning
confidence: 99%
“…Aorta-to-Pulmonary Artery Fistulas Aorta-to-pulmonary artery fistulas, often systemic-to-pulmonary and left-to-right shunts (Table), can be congenital (ie, PDA) or can result from a dissecting aneurysm (25)(26)(27)(28), Marfan syndrome (26), trauma or surgery (29)(30)(31), severe aortic stenosis (32,33), inflammatory aortitis (eg, giant cell arteritis) (34), and infection (eg, endocarditis, syphilis) (35)(36)(37). When acquired, they usually manifest acutely as a new continuous murmur in the setting of respiratory and cardiac failure.…”
Section: Aorta-systemic Vein Fistulasmentioning
confidence: 99%